The role of novel agents on the reversibility of renal impairment in newly diagnosed symptomatic patients with multiple myeloma - Dimopoulos, M.A.; Roussou, M.; Gkotzamanidou, M.; Nikitas, N.; Psimenou, E.; Mparmparoussi, D.; Matsouka, C.; Spyropoulou-Vlachou, M.; Terpos, E.; Kastritis, E. (Leukemia, 2013)
The role of thalidomide, bortezomib and lenalidomide in multiple myeloma patients presenting with renal impairment was evaluated in 133 consecutive newly diagnosed patients who were treated with a novel agent-based regimen. A significant improvement of renal function (≥renalPR (renal partial response)) was observed in 77% of patients treated with bortezomib, in 55% with thalidomide and in 43% with lenalidomide (P=0.011). In multivariate analysis, bortezomib-based therapy was independently associated with a higher probability of renal response compared with thalidomide-or lenalidomide-based therapy. Other important variables included eGFR (estimated glomerular filtration rate) ≥30 ml/min, age ≤65 years and myeloma response. Patients treated with bortezomib achieved at least renalPR in a median of 1.34 months vs 2.7 months for thalidomide and >6 months for lenalidomide-treated patients (P=0.028). In multivariate analysis bortezomib-based therapy, higher doses of dexamethasone (≥160 mg during the first month of treatment), an eGFR ≥30 ml/min and age ≤65 years were independently associated with shorter time to renal response. In conclusion, bortezomib-based therapies may be more appropriate for the initial management of patients with myeloma-related renal failure; however, thalidomide and lenalidomide are also associated with significant probability of improvement of their renal function. © 2013 Macmillan Publishers Limited All rights reserved.